LINKING ADMINISTRATORS ROLES IN CAREER PROGRAMS TO PROACTIVE BEHAVIOR AS A DETERMINANT OF EMPLOYEES PROMOTION OPPORTUNITIES - Azman Ismail; Eddy Madiono Sutanto (Jurnal Manajemen dan Wirausaha, 2017)
This research examines the relationship between administrators roles in career programs, proactive behavior and employees promotion opportunities. Self-administered questionnaires were collected from employees who work in an established private oil and gas firm in West Coast of Peninsular Malaysia. The outcomes of SmartPLS path model analysis demonstrate that the ability of administrators to plan and managecareer programs have strongly invoked employees proactive behavior. As a result, this situation may lead to an enhance employees promotion opportunities in the organizational sample. Further, this study offers discussion, implications and conclusion.